Exercise 5.
Find the solution of
dy/dx= e2x+y 2x+y
that has y = 0 when x = 0
Given equation,
"\\dfrac{dy}{dx}=e^{2x+y}"
"\\implies \\dfrac{dy}{dx}=e^{2x}.e^y"
"\\implies e^{-y} dy=e^{2x} dx"
Integrate Both the sides
"\\implies \\int e^{-y} dy=\\int e^{2x} dx"
"\\implies -e^{-y}=\\dfrac{e^{2x}}{2}+C"
As,y(0)=0,
"\\implies -e^{-0}=\\dfrac{e^0}{2}+C"
So "C=-1-\\dfrac{1}{2}=\\dfrac{-3}{2}"
So the solution is
"-e^{-y}=\\dfrac{e^{2x}}{2}-\\dfrac{3}{2}"
i.e. "e^{-y}=-\\dfrac{e^{2x}}{2}+\\dfrac{3}{2}"
Comments
Leave a comment